THE CONTRIBUTION OF SELF-REFLECTION IN PORTFOLIO TOWARD STUDENTS’ WRITING SKILLS - Tri Setyaningsih; Nurhandayani (ELLTER Journal, 2020)
Writing is considered to be a sequence of complicated process in which the students need to organize their ideas and develop them into a systematic order. Due to its complexity process, students often find problems in writing, such as idea organization, sentence arrangements, punctuation, and capitalization. Consequently, this study examined the essay writing class students of the undergraduate program to find out whether or not self-reflection in portfolio gives contribution in improving their writing skills. A questionnaire, observational field notes, and document of students’ self-reflections were used to collect data about the students’ awareness about self-refection, portfolio and writing based on their perspectives. The findings reveal that the self-reflection in portfolio indeed has given contribution toward students’ writing through a set of guided questions so that the students become more aware about their strengths and weaknesses in every draft of their writing. Knowing those things will eventually help students to produce better writing on their own that lead them to be autonomous learners.